Usage of ICT among Social Educators-An Analysis of Current Practice in Spain - Alejandro Martínez-Pérez; Fernando Lezcano-Barbero; Rebeca Zabaleta-González; Raquel Casado-Muñoz (MDPI AG, 2023)
The objective of this study is to identify the usage of ICT tools among social educators within their professional activity. Technology among social educators is currently a very up-to-date topic. This is a professional group with its own characteristics that are different from those of teachers or other professionals in formal education. A mixed sequential two-phase method was proposed for the study: both quantitative and qualitative. In the first phase, the EdSocEval_V2 questionnaire was applied to a sample of 504 social educators from 17 autonomous communities. In the second phase, four focus groups were formed. The results presented reduced and basic usage of ICT: in management and administrative tasks and for communication with conventional tools. The COVID-19 pandemic has likewise increased the need for the use of ICT in socio-educational interventions, although their use for intervention among these groups is still very scarce. Training in and raising awareness of ICT among professionals for social interventions are priorities, as is the construction of a referential framework for professional training.